PENGARUH HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA TOKO ALFAMIDI KEADILAN RAWA DENOK DI DEPOK JAWA BARAT - Rosaliana Gunawan, Isma; Haryantini (Journal of Research and Publication Innovation, 2024)
This research aims to determine the partial and simultaneous influence of price and promotion on consumer purchasing decisions at the Alfamidi Justice Rawa Denok store in Depok, West Java. The type of research method used is quantitative research, namely a research method based on the philosophy of positivism. This research had a population of 133,658 and a sample of 100 respondents. The sampling method uses Slovin theory, with an error rate of 10%. Some of the conclusions that the author put forward are as follows: Price partially has a significant influence on consumer purchasing decisions at the Alfamidi Justice Rawa Denok shop in Depok, West Java. This is proven by the determination value or influence contribution of 0.886 or 88,6% while the remaining 11,4% is influenced by other factors. Hypothesis testing obtained a calculated t value > t table or (27.587 > 1.984) with a significance value < 0.05 or (0.00 < 0.05). Promotion partially has a significant effect on consumer purchasing decisions at the Alfamidi Justice Rawa Denok store in Depok, Java. West. This is proven by the determination value or influence contribution of 0.869 or 86,9% while the remaining 13.1% is influenced by other factors. Hypothesis testing obtained a calculated t value > t table or (26.019 > 1.984) with a significance value < 0.05 or (0.00 < 0.05). Price and promotion simultaneously have a significant effect on consumer purchasing decisions at the Alfamidi Justice Rawa Denok store in Depok, West Java. This is proven by the simultaneous determination or contribution value of 0.914 or 91.4% while the remaining 8.6% is influenced by other factors. Hypothesis testing obtained calculated F value > F table or (543.775 > 3.094) with significance < 0.05 or (0.00 < 0.05)